Listening to fathers: Personal impacts of raising children with Down syndrome. (September 2019) - Marshak, Laura E; Lasinsky, Emily E; Williams, Courtney
The aim of this qualitative study was to contribute to an understanding of how biological fathers ( N = 311) believe having a child with Down syndrome has impacted them personally. Thematic analysis was used to derive meaning from responses to open-ended survey questions. In addition to describing personal impacts, fathers shared how their perspectives shifted over time and possible contributory factors. The results indicated that fathers were often deeply impacted by the experience of parenting a child with Down syndrome. The vast majority expressed positive changes in terms of personal growth; however, it is important to note that positive emotions often coexisted with more distressing ones such as anxiety and loss. Most fathers reported a positive trajectory in terms of their adjustment and many attributed it to learning that their negative assumptions about people with Down syndrome were not accurate. Implications for practitioners and researchers are discussed.